COVID-19: A black swan for foreign direct investment. Evidence from European countries - Eglantina Hysa; Erinda Imeraj; Nerajda Feruni; Mirela Panait; Valentina Vasile (Journal of Risk and Financial Management, 2022)
This study aims to reconsider the role of foreign direct investment determinants for European national development and to analyze the impacts of the pandemic situation caused by COVID-19. Foreign direct investment is a source of development; therefore, this study includes empirical applications, specifically the random effect model, for EU countries, during the pandemic period. This study provides some valuable conclusions regarding the changes caused by the main determinants of foreign direct investment, such as unemployment, interest rates, economic growth, inflation, and business confidence. Additionally, the proxies of COVID-19 are the number of cases and number of deaths, both appearing to positively contribute to FDI outflow, the former with a higher impact than the latter. Based on the availability of the data, this paper deals with 22 European Union countries for Q1, Q2, and Q3 of 2020. Data for all the chosen variables were not available for the fourth quarter (Q4); thus, this period was not considered, which constitutes a limitation of this study, but confirms the need for robust FDI inflows to support the sustainable post-pandemic development recovery of less-developed EU countries. As the need for external funding sources, i.e., FDI inflow, grows in times of crisis, governments should take suitable measures to uplift the confidence of socially responsible foreign investors during difficult times generated by black swan events. There is almost no detailed research regarding the impact of COVID-19 on FDI flows received by European Union countries.
Keywords: 330; COVID-19; EU countries; foreign direct investments; unemployment